TEST OF FORMATION WATER AND CHEMICAL COMPATIBILITY FOR REMOVAL OF MUDCAKE IN WELLBORE - Panca Wahyudi; Tjuwati Makmur (Testing Center for Oil and Gas LEMIGAS, 2004)
Laboratory and field studies indicate that almost every operation in the field, such as drilling, completion, workover, production and stimulation are potential source of damage to well productivity. Formation damage has long been recognized as a source of serious productivity reduction in many oil and gas reservoirs. The mud cake is a damage that occurs in formation caused by drilling process. Prevention of formation damage has the following advantages : a) To reduce ultimate completion costs; b) To preserve barriers; c) To improve sweep efficiency. Potassium chloride (KCI) and breaker are chemical materials used in mud clean up system to remove the mud cake formed in drilling process. In relation to this, it is very important to know whether the formation water and KCI solution, then the formation water and breaker, are compatible or not. This paper is written based on our experience in formation damage laboratory tests. Therefore, the main topic of this paper is